2020
DOI: 10.3389/fchem.2020.00623
|View full text |Cite
|
Sign up to set email alerts
|

2H/4H-Chromenes—A Versatile Biologically Attractive Scaffold

Abstract: 2H/4H-chromene (2H/4H-ch) is an important class of heterocyclic compounds with versatile biological profiles, a simple structure, and mild adverse effects. Researchers discovered several routes for the synthesis of a variety of 2H/4H-ch analogs that exhibited unusual activities by multiple mechanisms. The direct assessment of activities with the parent 2H/4H-ch derivative enables an orderly analysis of the structure-activity relationship (SAR) among the series. Additionally, 2H/4H-ch have numerous exciting bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(85 citation statements)
references
References 72 publications
0
85
0
Order By: Relevance
“…This compound, prepared for a previous study, demonstrated anti-parasitic action against both T. cruzi and L. amazonensis ( Martin et al, 2018 ). Chromene derivatives bearing trisubstituted amines were previously reported as antimycobacterial against M. tuberculosis H37Rv ( Raj and Lee, 2020 ). C10, the most active compound among the pyranocoumarin derivatives, differs from the others with the substituent group on the aryl moiety and the ester function on the pyran ring.…”
Section: Resultsmentioning
confidence: 99%
“…This compound, prepared for a previous study, demonstrated anti-parasitic action against both T. cruzi and L. amazonensis ( Martin et al, 2018 ). Chromene derivatives bearing trisubstituted amines were previously reported as antimycobacterial against M. tuberculosis H37Rv ( Raj and Lee, 2020 ). C10, the most active compound among the pyranocoumarin derivatives, differs from the others with the substituent group on the aryl moiety and the ester function on the pyran ring.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, cancer can be measured by assessing the degree of mitochondrial impairment and metabolic dysfunctions such as cellular energy supply, cell death signaling, irregulation of metabolic pathways, formation of reactive oxygen species (ROS), compromised enzyme actions, aerobic glycolysis augmented in tumor cells, alterations in lipid metabolism and unbalanced pH [ 6 ]. Therefore, to cure such metabolic dysfunctions, naturally occurring flavonoids, flavonols, flavanones (2-phenyl chroman-4-one derivatives) and homoisoflavanones exhibit good anticancer potential along with other pharmacological activities such as anti-inflammatory, antioxidative, antidiabetic, antibacterial, antimicrobial, antifungal, antimutagenic, antiparasitic and anti-HIV [ 7 , 8 ]. In this regard, the following naturally occurring flavanones such as naringenin [ 9 ], naringin [ 9 ], sakuranetin [ 10 ], eriodictyol [ 11 ], calyxin G, deguelin [ 12 ] and sterubin [ 13 ] have been reported (Figs.…”
Section: Biological Activities Of Chromanonementioning
confidence: 99%
“…Chromene moieties play a signi cant role with structural aryl sulfonamide scaffold which can be easily transformed into functionalized diverse biologically active molecules. 124 Naturally occurring 125 and synthetic chromene compounds possess antibacterial properties. 126 A number of pathways are available for their synthesis, but there is a signi cant need for approaches that include chromenes from precursors that are readily available.…”
Section: Chromene Moiety Containing Sulfonamide Derivativesmentioning
confidence: 99%